Яратӥ-а мон?: кылбуръёс, поэмаос, тодэ ваёнъёс / Георгий Архипов - Архипов Георгий Архипович (Удмуртия, 2014)
Экземпляры: ф11 (20180913) / Инвентарный номер: 56200 / Цена: 25.00 / Сис.шифр: С(удм) / Авт.знак: А 87 / ГРНТИ: 17.82.10 / ББК: 84(2Рос= Удм)